Enterprise Governance of Information Technology Achieving Strategic Alignment and Value - Van Grembergen, Wim; De Haes, Steven (Springer US : Imprint: Springer, 2009)
Enterprise governance of IT is a relatively new concept that is gaining traction in both the academic and practitioner worlds. Going well beyond the implementation of a superior IT infrastructure, enterprise governance of IT is about defining and embedding processes and structures throughout the organizations that enable both business and IT people to execute their responsibilities, while maximizing the value created from their IT-enabled investments. At the forefront of the field, the authors draw from years of research and advising corporate clients to present the first comprehensive resource on the topic. Featuring numerous case examples from companies around the world, the book integrates theoretical advances and empirical data with practical application, including in-depth discussion of such frameworks as COBIT and VALIT, which are used to measure and audit the value of IT investments and ensuring regulatory compliance. A variety of elements, including executive summaries and sidebars, extensive references, and questions and activities (with additional materials available on-line) ensure that the book will be an essential resource for professionals, researchers, and students alike. "At last we have a solidly research-based text on the enterprise governance of IT that successfully fuses business and IT perspectives. With its emphasis on the creation of business value, and on the use of relevant metrics, this book offers a distinctive view of these key processes. The authors, whose reputation and experience in the field is second to none, have created a guide to the strategic management of IT that will be an essential source for managers." Professor James W. Bryant Centre for Individual & Organisational Development Sheffield Hallam University United Kingdom "IT governance is a hot topic today and this book provides a wealth of practical and useful information. Regardless of whether you are concerned about compliance issues, or worried about the alignment of your IT investment with the corporate goals, this book will provide guidance to assist your efforts. As well as academic models and practice oriented frameworks such as CobiT, Val-IT and balanced scorecard, the volume includes recent case studies illustrating how the concepts and frameworks are applied in real life companies. I strongly recommend this book to Corporate and IT Managers as well as MBA and IT Graduate students." Aileen Cater-Steel, Ph.D Senior Lecturer (Information Systems) School of Information Systems University of Southern Queensland Australia.